Visual Perception Of The Volumetric Form And Its Interpretation In The Educational Drawing Of The Head At The Initial Stage Of Learning - Djalolova Dilafruz Fattoxovna; Saidova Хulkar Хamidovna (Genius Journals, 2023)
This article is devoted to the peculiarities of the perception of the volumetric form and its interpretation in the educational pattern of the head at the initial stage of training. The volume form is difficult to read, which determines the relevance of the article.
Keywords: Academic drawing; High Renaissance; artist-designer; the volume-constructive shape of the head